FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING DI PERUSAHAAN MANUFAKTUR - Eka , Dedy Agusvian; Salim, Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study is to obtain empirical evidence regarding the effect of growth opportunity, cash flow, net working capital, and capital expenditure on cash holding in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This research used 152 samples and 456 data from manufacturing companies selected by purposive sampling method. The data in this research were inputted and calculated using the Microsoft Excel program and processed using the Eviews 10 program. The results of this study indicate that growth opportunity and capital expenditure have a significant negative effect on cash holding, while cash flow and net working capital have an insignificant positive effect on cash holding.